2022
DOI: 10.1213/ane.0000000000005915
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Versus Midazolam Premedication and Postoperative Negative Behavioral Changes in Younger Children: A Randomized Controlled Trial

Abstract: BACKGROUND: Postoperative negative behavioral changes (NBCs) are common among children, but risk for this is thought to be reduced with premedication. Midazolam has for many years been a standard premedication for children. More recently, the alpha-2 adrenergic agonist clonidine has also become popular as a preanesthetic sedative. We hypothesized that clonidine was superior to midazolam for limiting new NBCs in children as assessed using the Post Hospital Behavior Questionnaire (PHBQ). METHODS: This was a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…13,14 The details concerning this outcome have been presented earlier. 10 day at home, rescue morphine directly postoperatively, and adverse events including new symptoms for prolonged nausea/vomiting within the first week. Instruments used for pain scoring were Face Legs Activity Cry Consolability (FLACC) 15,16 and Faces Pain Scale-Revised (FPS-R).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 The details concerning this outcome have been presented earlier. 10 day at home, rescue morphine directly postoperatively, and adverse events including new symptoms for prolonged nausea/vomiting within the first week. Instruments used for pain scoring were Face Legs Activity Cry Consolability (FLACC) 15,16 and Faces Pain Scale-Revised (FPS-R).…”
Section: Discussionmentioning
confidence: 99%
“…The PHBQ outcome definition used here is explained in some depth in the original trial publication. 10 Premedication can be useful for calming an anxious child and to get a smooth anesthesia induction, but this may not affect the development of meaningful postoperative NBCs. Exactly what causes post-NBCs can be multifactorial and differ from child to child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Midazolam is primarily an anxiolytic drug [7 ▪▪ ,8 ▪▪ ] and, at least in children, the sedative properties are moderate at best. In a dose-finding study with the oral cyclodextrin-based preparation ozalin, no additional sedation could be achieved with doses of more than 0.25 mg/kg [9].…”
Section: Premedicationmentioning
confidence: 99%
“…Dexmedetomidine is considered to be a suitable [12 ▪ ] or even superior agent [13] for premedication compared with midazolam; this judgement was mainly based on the observation of more peaceful recovery and improved postoperative analgesia. However, recently two articles comparing midazolam with clonidine [7 ▪▪ ] and midazolam with clonidine and dexmedetomidine [8 ▪▪ ] showed that α 2 -agonists cause marked sedation, but virtually no anxiolysis. Anxiolysis (what we usually want) and sedation (what we can easily see) are not the same entities.…”
Section: Premedicationmentioning
confidence: 99%